Hölderlin – der Dichter des Dichters. Im Anhang: Grundzüge von Hölderlins Homburger Poetologie (Studia theodisca, 2014)
Revising Heidegger’s dictum about Hölderlin being «the poet’s poet» and the philosopher’s remarks on the «essence» of poetry, the emphasis is shifted on the “method” of poetry, a crucial question for Hölderlin, which is here analyzed on the basis of his “Homburg poetology” (cfr. the table in the appendix) as well as of his poetry and prose.